Parents With Mental Illness: Parental Coping Behavior and Its Association With Children's Mental Health - Sell, Marlit; Radicke, Alina; Adema, Bonnie; Daubmann, Anne; Kilian, Reinhold; Stiawa, Maja; Busmann, Mareike; Winter, Sibylle M.; Lambert, Martin; Wegscheider, Karl; Plass-Christl, Angela; Wiegand-Grefe, Silke (Frontiers in Psychiatry, 2021)
The relevance of coping behavior for the individual’s own mental health has been widely investigated. However, research on the association between coping of parents with a mental illness and their children’s mental health is scarce. In the current study, we address the role of several parental coping strategies and their relation to child psychological symptoms. As part of the German randomized controlled multicenter study CHIMPS (children of mentally ill parents), parents with mental illness completed questionnaires on illness-related coping and child mental health symptoms. Children’s diagnoses of a mental disorder were assessed with diagnostic interviews. The sample comprised n = 195 parents with mental illness and n = 290 children and adolescents aged 4 to 18 years. We conducted mixed models to investigate the associations of parental coping strategies with internalizing and externalizing symptoms as well as the diagnosis of a mental disorder in children controlling for sociodemographic factors and parental symptom severity. Parental coping characterized by religiosity and quest for meaning was significantly associated with fewer mental health symptoms and lower odds of a mental disorder in children, whereas a depressed processing style was related to increased internalizing problems in the children. Coping behavior in parents with mental illness is a relevant factor for the mental health of their children and should be considered in preventive interventions.